Paradoks Kebebasan Beragama di Indonesia: Antara Ketertiban Sosial dan Hukum Negara - Marsha Odelia; Citra Ayu Deswina Maharani; Dina Ramadhani; Melinda Melinda; Elviandri Elviandri (Prodi Tata Negara (Siyasah) IAIN Langsa, 2025)
Restrictions on freedom of religion within Indonesia’s legal system continue to generate normative and practical debates, particularly due to regulatory practices that tend to be repressive and discriminatory toward certain religious groups. This situation reflects an ongoing tension between the protection of fundamental rights and the state’s interest in maintaining social order. This study aims to analyze freedom of religion in Indonesia from a utilitarian perspective, specifically through John Stuart Mill’s harm principle, and to propose a legal reformulation oriented toward justice and the promotion of the common good. The research employs a normative legal method using philosophical and conceptual approaches, drawing on statutory regulations, legal doctrines, and utilitarian legal philosophy. The findings indicate that current restrictions on religious freedom in Indonesia are inconsistent with utilitarian principles, as they often undermine the greatest happiness of those affected without clear evidence of actual harm to society at large. The proposed legal reform includes revising discriminatory regulations, simplifying the licensing procedures for houses of worship in a non-discriminatory manner, and accelerating the establishment of a National Regulatory Body as a mechanism for legal harmonization. The application of the harm principle in public policymaking has significant implications for strengthening the protection of religious freedom, balancing individual liberty with social order, and fostering a more just and welfare-oriented legal system.